PERANAN ORGANIZATIONAL CITIZE DALAM MEMEDIASI PENGARUH JO DAN HUMAN RESOURCES MANAGE TERHADAP SERVICE QUALITY PADA BINTANG LIMA DI JAKARTA SHIP BEHAVIOR SATISFACTION ENT PRACTICES EBUAH HOTEL PUSAT - DEWAYANI HAPSARI (Jurnal Manajemen dan Pemasaran Jasa, 2009)
The purpose of this research is to propose a model which organizational citizenship behavior and job performance mediate the influence of job satifaction and human resources management practices toward service quality at Grand Sahid Jaya Jakarta. The conceptual framework consists of the following constructs : job satisfaction, human resources management practices, organizational citizenship behavior, job performance, and service quality. Moreover, four hypotheses were developed and tested. instrument test of validity and reliability were used to test the validity of the measures, while multiple regression from Statistical Package forSocial Science (SPSS) was used in hypotheses testing. Data were collected from Grand Sahid Jaya employee, Jakarta. The objectives of this research is to analyze the j.b satisfaction influence organizational citizenship behavior at Grand Sahid Jaya Jakarta, analyze the human resources practices toward organizational citizenship behavior, analyze the organizational citizenship behavior influence job performance and analyze job performance influence service quality at Grand Sahid Jaya JakarIta. The result indicate that all hypothesis was supported, indicated that job sati action have significant influence toward organizational citizenship behavior, human resources practices have significant influence toward organizational citizenship behavior, organizational citizenship behavior have significant influence toward job performance and job performance have significant influence toward service quality.Keywords : Job performance, service quality, job satisfaction, and organizational citizenship behavior.